Calculation method and mechanism of ultimate side resistance of screw pile. Issue 1 (2nd January 2023) - Ma, Hong-wei; Liu, Li; Wang, Peng; Yuan, Song; He, Qing-rui; Yang, Xiao-li
Abstract: A calculation method of the ultimate side resistance of screw pile is established by regarding the soil slip surface under screw thread as a logarithmic slip surface, and its accuracy is proved by a model test and a situ test. The shape of soil slip surface around a screw pile has three possible types, including a cylinder with a diameter equal to the pile's outer diameter, intersected and separated of logarithmic spiral. The shape of the screw pile is determined by the first critical pitch and the second critical pitch. The screw thread geometry including screw pitch, the effective screw thread width and the dip angle of thread surface have a significant effect on the side resistance enhancement factor of screw pile. No matter how the form of screw thread is changed, the side resistance enhancement factor is always larger when the pitch is taken as the second critical pitch. To improve the ultimate lateral resistance of a screw pile, a smaller dip angle of thread surface and a larger effective screw thread width should be selected to obtain a larger second critical pitch, and screw pitch should be selected as close as possible to the second critical pitch.